Effect of Incorporating 1 Avocado per Day Versus Habitual Diet on Vascular Function in Adults With Abdominal Obesity: An Ancillary Study of HAT, a Randomized Controlled Trial - Kristin M. Davis; Kristina S. Petersen; Nirupa R. Matthan; Richard S. Legro; Penny M. Kris‐Etherton (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Abdominal obesity is associated with endothelial dysfunction and poorer vascular health. Avocado consumption improves postprandial endothelial function; however, the longer‐term effects remain unclear. It was hypothesized that the daily addition of 1 avocado to a habitual diet for 6 months would improve flow‐mediated dilation (FMD) and carotid–femoral pulse wave velocity in individuals with abdominal obesity (waist circumference ≥35 in for women, ≥40 in for men), compared with a habitual diet low in avocados. Methods and Results HAT (Habitual Diet and Avocado Trial) was a multicenter, randomized, controlled, parallel‐arm study that investigated the health effects of adding 1 avocado per day to a habitual diet in individuals with abdominal obesity. At the Pennsylvania State University, University Park study center (n=134; age, 50 ± 13 years; women, 78%; body mass index, 32.6 ± 4.8 kg/m2), markers of vascular function were measured, including endothelial function, assessed via brachial artery flow‐mediated dilation, and arterial stiffness, assessed via carotid–femoral pulse wave velocity. Between‐group differences in 6‐month change in flow‐mediated dilation and carotid–femoral pulse wave velocity were assessed using independent t tests. Prespecified subgroup analyses were conducted using linear regression. No significant between‐group differences in flow‐mediated dilation (mean difference=−0.62% [95% CI, −1.70 to 0.46]) or carotid–femoral pulse wave velocity (0.25 m/s [95% CI, −0.13 to 0.63]) were observed. Results of the subgroup analyses were consistent with the primary analyses. Conclusions Longer‐term consumption of 1 avocado per day as part of a habitual diet did not improve measures of vascular function compared with a habitual diet low in avocados in individuals with abdominal obesity. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT03528031.